PENGARUH VARIASI JARAK ELEKTRODA PADA METODE ELEKTROKOAGULASI DALAM PENGOLAHAN LIMBAH CAIR BATUBARA - Dewi, Alya Triana; Alim, Muhammad Syahirul; Khair, Riza Miftahul; Abdi, Chairul (Jernih: Jurnal Tugas Akhir Mahasiswa, 2025)
Coal stockpiling activities in the stockpile produce coal stockpile wastewater which contains pollutants so that it needs to be processed before being released into the environment so as not to cause pollution in accordance with the regulations in South Kalimantan Governor Regulation No. 36 of 2008 concerning Coal Wastewater Quality Standards. This study aims to analyze the results of the quality test of coal effluent after being treated by the electrocoagulation method in meeting environmental quality standards and to analyze the effect of the electrode distance used in the electrocoagulation method on the treatment of coal effluent. This research method is in the form of electrocoagulation, the wastewater treatment process using direct electricity and the electrode is an Aluminum (Al) plate with dimensions of 20 cm x 10 cm and a thickness of 0.5 mm. The parameters were Total Suspended Solid (TSS), pH, iron (Fe) and manganese (Mn) with variations in electrode distance of 1 cm, 2 cm, and 3 cm with a contact time of 90 minutes. The voltage used is 12 volts and the current is 10A. The results showed that the electrocoagulation process with an electrode distance of 1 cm was the most efficient in reducing pollutant levels, in the pH parameter the value increased from 5.36 to 7.23, in the TSS parameter the efficiency value reached 99.97% with a reduction in levels from 4305 mg. /L to 1.33 mg/L, on the iron (Fe) parameter the efficiency value reached 99.95% with a reduction in levels from 53 mg/L to 0.02 mg/L and on the manganese (Mn) parameter the efficiency value reached 99.85% with a reduction in levels from 20.32 mg/L to 0.031 mg/L. The results showed that each parameter after the electrocoagulation method was in accordance with environmental quality standards.